DOCUMENTATION OF LANDSLIDES AND INACCESSIBLE PARTS OF A MINE USING AN UNMANNED UAV SYSTEM AND METHODS OF DIGITAL TERRESTRIAL PHOTOGRAMMETRY. - Kapica, Roman (GeoScience Engineering, 2015)
Abstract Quite a big boom has recently been experienced in the technology of unmanned aerial vehicles (UAV). In conjunction with optical correlation systems, it gives one a powerful tool for the creation of digital terrain models and orthophotomaps. This system was used for the documentation of landslides and inaccessible parts of the Nástup Tušimice mine in the North Bohemian Brown Coal Basin (CzechRepublic). The images were taken by the GATEWING X100 unmanned system that automatically scans an area of interest. For detailed documentation of selected parts of the mine, we used the method of digital terrestrial photogrammetry. The main objective was to find a suitable measurement technology for operational targeting of landslides and inaccessible parts of the mine, in order to prepare the basics for remediation work. Abstrakt Poměrně velký rozmach zažívá v poslední době technologie bezpilotních leteckých prostředků (UAV). Ve spojení s optickými korelačními systémy získáme kvalitní nástroj pro tvorbu digitálního modelu terénu a ortofotomapy. Uvedený systém jsme použili pro dokumentaci sesuvných a nedostupných části lomu v lokalitě Doly Nástup Tušimice v Severočeské hnědouhelné pánvi (Česká republika). Snímky byly pořízeny bezpilotním systémem GATEWING X100, který automaticky nasnímá zájmové území. Pro podrobnou dokumentaci vybraných částí lomu jsme použili metodu digitální pozemní fotogrammetrie. Hlavním cílem měření bylo vytipovat vhodnou technologii pro operativní zaměřování sesuvů a nedostupných částí lomu, za účelem vyhotovení podkladu pro sanační práce.